Soil Tillage Affected Weed Community and The Growth and Yield of Soybean for Edamame Production - Irawati Chaniago; Aswaldi Anwar; Rahmi Azhari (Journal of Applied Agricultural Science and Technology, 2023)
Edamame has been known as a vegetable soybean that is highly nutritious and has become popular in Indonesia. As for other crops, soybean cannot avoid the presence of weedy plants in the field. The study reported here aimed at determining the effect of tillage on weed and the growth and yield of soybean for edamame production. A randomized completely block design (RCBD) with three repetitions was used for the three tillage systems (zero, reduced, and conventional tillage). Data of soybean growth and yield component were collected and analysed with analysis of variance and mean separation of DNMRT at 5% level. Results show that most growth and yield parameter components (plant height, number of primary branches, number of leaves, number of pods per plant, pod weight per plant, number of seeds per plant, and yield) were highest in favor of reduced tillage system. The highest yield of edamame soybean (13.50 ton ha-1) was observed in the treatment group of reduced tillage and the effect was similar to that of conventional tillage (13.29 ton ha-1). Reduced and conventional tillage resulted in the emergence of new weed species such as Digitaria sanguinalis and Synedrella nodiflora with the total SDR value for all treatment groups of 54.38% and 37.74%, respectively. In contrast, the application of herbicide glyphosate prior to land cultivation has completely controlled Napier grass (Pennisetum purpureum Schumach.) and rough Mexican clover (Richardia scabra L.).